Duplication of Dio3 genes in teleost fish and their divergent expression in skin during flatfish metamorphosis - Alves, Ricardo (2019)
Deiodinase 3 (Dio3) plays an essential role during early development in vertebrates by controlling tissue thyroid hormone (TH) availability. The Atlantic halibut (Hippoglossus hippoglossus) possesses duplicate dio3 genes (dio3a and dio3b). Expression analysis indicates that dio3b levels change in abocular skin during metamorphosis and this suggests that this enzyme is associated with the divergent development of larval skin to the juvenile phenotype. In larvae exposed to MMI, a chemical that inhibits TH production, expression of dio3b in ocular skin is significantly up-regulated suggesting that THs normally modulate this genes expression during this developmental event. The molecular basis for divergent dio3a and dio3b expression and responsiveness to MMI treatment is explained by the multiple conserved TREs in the proximal promoter region of teleost dio3b and their absence from the promoter of dio3a. We propose that the divergent expression of dio3 in ocular and abocular skin during halibut metamorphosis contributes to the asymmetric pigment development in response to THs. (C) 2017 Elsevier Inc. All rights reserved.